Day 2 Tue, October 27, 2020 2020
DOI: 10.2118/204265-stu
|View full text |Cite
|
Sign up to set email alerts
|

3D Visualization of Oil Displacement in Porous Media by the Injection of Microcapsule Suspension using Confocal Microscopy

Abstract: In the past decades, oil companies have shown growing interest in increasing oil recovery efficiency. Commonly, after primary and secondary recovery phases, a large amount of oil remains trapped inside the reservoir. Thus, the number of studies focused on enhanced oil recovery is growing, aiming to increase the recovery factor. The focus of this work is to study the fundamentals of oil displacement in porous media using a confocal laser scanning microscope, which enables 3D visualization of dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The injection of the microcapsules into 38%-porosity and 232D-permeability homogeneous porous media made of glass spheres allowed for the mobilization of residual oil saturation (immobile oil), which was visually proven by using confocal microscopy (Figure 15). In fact, it was shown that within an 11 mm-length porous model, the injection of microcapsules allowed for a reduction in the residual oil saturation from 32.9 to 25.7% [69]. Unfortunately, the images presented in the paper demonstrate that even in high-permeability porous channels, the deep penetration of microcapsules is problematic.…”
Section: Plugging Behavior Of Gellan Gum In Laboratory Experimentsmentioning
confidence: 90%
See 1 more Smart Citation
“…The injection of the microcapsules into 38%-porosity and 232D-permeability homogeneous porous media made of glass spheres allowed for the mobilization of residual oil saturation (immobile oil), which was visually proven by using confocal microscopy (Figure 15). In fact, it was shown that within an 11 mm-length porous model, the injection of microcapsules allowed for a reduction in the residual oil saturation from 32.9 to 25.7% [69]. Unfortunately, the images presented in the paper demonstrate that even in high-permeability porous channels, the deep penetration of microcapsules is problematic.…”
Section: Plugging Behavior Of Gellan Gum In Laboratory Experimentsmentioning
confidence: 90%
“…Moreover, no pressure gradient data were presented in this paper; however, from the figure above, it is evident that the gel microcapsules plug the porous media. Almost in all tests, the gellan gum was injected in the form of a solution; however, in [69], the gellan gum was used to prepare 104 µm-diameter microcapsules with a soft 5 µm-thickness shell, which presumably allowed for better penetration into 120-200 µmsize pores [69]. The injection of the microcapsules into 38%-porosity and 232D-permeability homogeneous porous media made of glass spheres allowed for the mobilization of residual oil saturation (immobile oil), which was visually proven by using confocal microscopy (Figure 15).…”
Section: Plugging Behavior Of Gellan Gum In Laboratory Experimentsmentioning
confidence: 99%